ลักษณะของภาพยนตร์สารคดีที่แสดงอัตวิสัยของไมเคิล มัวร์ - ธนพล น้อยชูชื่น (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This research aims at analyzing Michael Moore’s subjective style in documentary films in terms of content and cinematic techniques. This is basically a qualitative research using textual analysis of 6 documentary films made by Michael Moore which were released in theaters and can be accessed in DVD or VCD format in Thailand. Additional data are collected from documents and online media. The results of the findings are as follows. 1)Michael Moore’s unique style is influenced by several factors, ranging from his family background (middle class Catholic), his appreciation for social protest, his interest in a variety of skills, to his sarcastic sense of humor and explicit expression of worldview. 2)The content of Moore’s documentaries demonstrates an outright opposition for Capitalism which is implicated in various forms depending on the issues raised by each documentary. This content is presented through the use of binary opposition: vice vs. virtue. The fight usually ends up in the loss and tragedy of the people involved to urge the audience to take action that would bring about changes in the problematic issues. 3)As regards the presentation or cinematic techniques, Moore is obviously influenced by the subjective style of documentary filmmaking evolved from the propaganda films of Soviet Socialism and Nazi, in addition to the stark realism of Direct Cinema style. Combining his uniqueness both in his own personality and skills with the individual documentary features, his films reflect the ultimate subjectivity in style that can not be comparable to other filmmakers.